FENOTIP DAN PRODUKTIVITAS BEBERAPA VARIETAS UNGGUL BARU PADI PADA AGROEKOSISTEM LAHAN SAWAH DI KABUPATEN MAJALENGKA - Yati Haryati; Irma Noviana (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2020)
Phenotype and Productivity of Several New High Yielding Rice Varieties in the Wetland Agro-ecosystem in Majalengka District. The high yielding varieties that have good adaptability to certain growing environments can be introduced for the development of productive, effective and efficient rice farming in the future. The adaptation assessment of new varieties was carried out in Jatitengah Village, Jatitujuh Sub District, Majalengka District in the first dry season (April to July 2017). The study activities used a Randomized Block Design (RBD), with treatments consisting of 5 varieties, namely Inpari 38, 39, 41, 42 and 43 with 5 replications. The study was conducted on farmers' land with treatment plots adjusted to the farmer’s natural plots. The parameters observed were plant height, number of productive tillers, number of panicles per clump, panicle length, number of filled grains per panicle, number of empty grains per panicle, weight of 1000 grains and productivity. Agronomic performance data were analyzed using the Duncan Test followed by multiple distance test (DMRT) using SAS version 9.0 for windows and farm analysis was measured by the R/C value. The results of the study showed that there was agronomic diversity in plant growth and the number of productive tillers and yields and components of rice yield among varieties. Inpari 43 variety provided productive tillers, panicle lengths, number of filled grains per panicle, number of empty grains per panicle which were higher than other varieties. The productivity of this variety was 7.70 t.ha-1, and R/C value of 2.20. Therefore, Inpari 43 can be used as an alternative to rotating varieties in the same agroecosystem and season in the paddy fields of Majalengka District.Keywords: rice, new high yielding varieties, paddy fieldsABSTRAK Varietas unggul baru (VUB) yang mempunyai daya adaptasi baik terhadap lingkungan tumbuh tertentu dapat diintroduksikan untuk pengembangan usahatani padi yang produktif, efektif dan efisien pada masa yang akan datang. Pengkajian adaptasi VUB dilaksanakan di Desa Jatitengah, Kecamatan Jatitujuh, Kabupaten Majalengka pada MKI (Bulan April - Juli 2017). Kegiatan pengkajian menggunakan Rancangan Acak Kelompok (RAK), dengan perlakuan 5 (lima) varietas, yaitu Inpari 38, 39, 41, 42, dan 43 dengan 5 (lima) ulangan. Kajian dilakukan di lahan milik petani dengan petak-petak perlakuan disesuaikan dengan petak alami. Parameter yang diamati tinggi tanaman, jumlah anakan produktif, jumlah malai per rumpun, panjang malai, jumlah gabah isi per malai, jumlah gabah hampa per malai, bobot 1000 butir dan produktivitas. Data keragaan agronomis dianalisis menggunakan Uji Duncan dilanjutkan dengan uji jarak berganda (DMRT) menggunakan SAS versi 9.0 for windows dan analisis usahatani diukur dengan nilai R/C. Hasil kajian menunjukkan bahwa terdapat keragaman agronomi dalam pertumbuhan tanaman dan jumlah anakan produktif maupun hasil dan komponen hasil tanaman padi antar VUB. Varietas Inpari 43 memberikan jumlah anakan produktif, panjang malai, jumlah gabah isi per malai, jumlah gabah hampa per malai relatif lebih baik dibandingkan varietas lainnya. Produktivitasnya mencapai 7,70 t/ha dan nilai R/C 2,20. Dengan demikian, VUB Inpari 43 dapat dijadikan alternatif untuk pergiliran varietas pada agroekosistem dan musim yang sama di lahan sawah Kabupaten Majalengka.Kata kunci: padi, varietas unggul baru, lahan sawah